Study on the energy scavenging from household air conditioning unit - Rahman, H. Y.; Rahman, M. M.; Howe, L. C.; Yew, F. C. (Universitas Islam Riau Indonesia, 2010)
This paper presents the design and construction of an energy scavenging system from a household air conditioning unit. The scavenged energy is used to heat up water for domestic purposes. The system consists of the condenser of a household air conditioning unit (existing), a pump, a plate heat exchanger, and a hot water storage tank. The condenser unit of a household air conditioner is modified to enable the flow of hot compressed refrigerant coming out from the compressor through the plate heat exchanger. The superheated portion of the heat is continuously absorbed by the water inside the hot water storage tank. Experimental investigation showed that this system can heat up water from room temperature to 82ºC within 9 hours of operation (8:00 am to 5:00 pm). By using this type of energy scavenging device, compressor efficiency can be improved and at the same time, hot water for domestic purposes can continuously be obtained free of charge. The end result is faster cooling and prolonged compressor life. This system is simple yet affordable and able to save water heating cost and environment friendly, i.e., less heat is rejected to the environment.